Management of Psoriasis - ERGUN, SAFİYE ATLAS TÜLİN (GALENOS YAYINCILIK, 2015)
Current data has led to better understanding of impact of psoriasis on quality of life as well as its physical and psychosocial co-morbidities. Consequently, holistic approach is mandatory in appropriate management of patients with psoriasis. Dermatologists should not only treat dermatological findings and symptoms but also screen patients regularly for co-morbidities and be active in coordinating the treatment if co-morbidities exist. Current review highlights main steps in management of psoriasis with a special emphasis on important practical points.
Keywords: Psoriasis; management; co-morbidity screening; PHYSICIANS GLOBAL ASSESSMENT; CARDIOVASCULAR RISK-FACTORS; QUALITY-OF-LIFE; PLAQUE PSORIASIS; METABOLIC SYNDROME; SEVERITY INDEX; SKIN DISEASES; THERAPY; PREVALENCE; RECOMMENDATIONS